Themes and Evolution of Misinformation During the Early Phases of the COVID-19 Outbreak in China—An Application of the Crisis and Emergency Risk Communication Model - Lu, Jiahui (Frontiers in Communication, 2020)
Social media has enabled misinformation to circulate with ease around the world during the novel coronavirus disease 2019 (COVID-19) pandemic. This study applies the Crisis and Emergency Risk and Communication model (CERC) to understand the themes and evolution of misinformation on the Internet during the early phases of the COVID-19 outbreak in China, when the epidemic developed rapidly with mysteries. Drawing on 470 misinformation rated as false by three leading Chinese fact-checking platforms between 1 January and 3 February 2020, the analysis demonstrated five major misinformation themes surrounding COVID-19: prevention and treatment, crisis situation updates, authority action and policy, disease information, and conspiracy. Further trend analyses found that misinformation emerged only after the nationwide recognition of the crisis, and appeared to evolve relating to crisis stages, government policies, and media reports. This study is the first to apply the CERC model to investigate the primary themes of misinformation and their evolution. It provides a standard typology for crisis-related misinformation and illuminates how misinformation of a particular topic emerges. This study has significant theoretical and practical implications for strategic misinformation management.